2010
DOI: 10.1021/ct100481h
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Molecular Mechanics Force Fields for RNA Simulations: Stability of UUCG and GNRA Hairpins

Abstract: The RNA hairpin loops represent important RNA topologies with indispensable biological functions in RNA folding and tertiary interactions. 5′-UNCG-3′ and 5′-GNRA-3′ RNA tetraloops are the most important classes of RNA hairpin loops. Both tetraloops are highly structured with characteristic signature three-dimensional features and are recurrently seen in functional RNAs and ribonucleoprotein particles. Explicit solvent molecular dynamics (MD) simulation is a computational technique which can efficiently complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
224
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 361 publications
(228 citation statements)
references
References 85 publications
4
224
0
Order By: Relevance
“…It has been observed that penalizing high-anti conformers can also lead to a flattening of the A-helix geometry. 9 The results shown in Fig. 3 suggest that small adjustments to α and ζ angles can improve the agreement with experiments of the Amberχ OL3 force field.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…It has been observed that penalizing high-anti conformers can also lead to a flattening of the A-helix geometry. 9 The results shown in Fig. 3 suggest that small adjustments to α and ζ angles can improve the agreement with experiments of the Amberχ OL3 force field.…”
mentioning
confidence: 57%
“…2 While simulations initialized in the vicinity of the native state are stable on short time-scales under a variety of simulation conditions, [3][4][5][6][7][8] more recent works strongly suggest that these systems are not correctly modeled by the current Amber force field. [9][10][11][12][13][14] Although different improvements have been proposed, 15 there is growing evidence that none of the available corrections are able to capture the crucial non-canonical interactions present in these tetraloops. 12,13 Despite their small size, an ergodic sampling of these systems requires substantial computational resources, in the order of hundreds of µs using massively parallel simulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional MD simulations were performed using a well-established protocol used for several other endonucleases (31), using the Amber ff12SB force field, which includes the ff99bsc0 corrections for DNA (32) and the ff99bsc0+χOL3 corrections for RNA (33,34). The Åqvist (35) force field has been used for Mg ions.…”
Section: Methods Summarymentioning
confidence: 99%
“…To test this notion and provide a window into the rapid (sub-microsecond), small-scale dynamics of the ribozyme, not easily accessible by experimental techniques (Ditzler et al 2010), we performed MD simulations on the crystallized trans-acting precursor using our established protocols (Krasovska et al 2005(Krasovska et al , 2006Rhodes et al 2006;McDowell et al 2007McDowell et al , 2010Sefcikova et al 2007a,b;Ditzler et al 2010). We used the latest parmbsc0χ OL3 (Perez et al 2007;Zgarbova et al 2011) variant of the Cornell et al AMBER force field (Cornell et al 1995), which is essential for stable RNA simulations (Banas et al 2010). We analyzed 49 simulations with an aggregate 1.8 µsec of simulation time (Table 2).…”
Section: Resultsmentioning
confidence: 99%